Boosting the solar water oxidation performance of a BiVO4 photoanode by crystallographic orientation control. Issue 5 (26th March 2018) - Han, Hyun Soo; Shin, Sun; Kim, Dong Hoe; Park, Ik Jae; Kim, Ju Seong; Huang, Po-Shun; Lee, Jung-Kun; Cho, In Sun; Zheng, Xiaolin
Abstract : A BiVO4 with a preferred [001] orientation and exposed {001} facets were grown epitaxially on FTO via a laser ablation, achieving the state-of-the-art photoelectrochemical performance for solar water-oxidation. Abstract : Materials with low crystal symmetry often exhibit anisotropic properties, allowing the tuning of their physical and chemical properties via crystallographic orientation and exposed facet control. Herein, for the first time, we have demonstrated that pristine BiVO4 with a preferred [001] growth orientation and exposed (001) facets exhibits excellent intrinsic charge transport properties and surface reactivity. Using preferentially [001]-oriented BiVO4 (p-BVO) as a photoanode for photoelectrochemical water splitting, an impressive photocurrent density at 1.23 V vs. the reversible hydrogen electrode (RHE) is achieved, which is approximately 16 times higher than that exhibited by a photoanode based on randomly oriented BiVO4 . Importantly, when the surface of p-BVO is further roughened and decorated with an oxygen evolution electrocatalyst, photocurrent densities of ∼3.5 and ∼6.1 mA cm −2 are achieved at 0.6 and 1.23 VRHE, respectively; the latter value corresponds to ∼82% of the theoretically achievable photocurrent density for BiVO4 under 1 sun illumination. Our results demonstrate the effectiveness of crystal orientation and exposed facet control in optimizing materials for solar water-splitting applications.